Experimental Investigations of Extracted Rapeseed Combustion Emissions in a Small Scale Stationary Fluidized Bed Combustor - Dieter Steinbrecht; Tristan Vincent; Nguyen Dinh Tung (Energies, 2009)
The objective of this study was to observe the combustion process of extracted rapeseed (ER) grist in a stationary fluidized bed combustor (SFBC) and evaluate the chemical compositions of the flue gas emissions. The experimental tests of ER combustion in the 90 to 200 kW (Kilowatt) SFB combustion test facility show that the optimal ER combustion temperature is within the range from 850 to 880° C. Temperature and the concentration of exhausted emissions (e.g. O2, CO, CO2, NO, NO2, SO2, Corg) were measured with dedicated sensors distributed within the combustor, along its height and in the flue gas duct. The experimental results showed that with respect to German emission limits the concentration of SO2 and NOx in the flue gas were high whereas that of CO was low. This study furthermore is applicable for the abundant biomass residue resources in Vietnam (rice husk, rice straw, bagasse, cassava residues, coconut shell etc.), which have similar chemical compositions to ER.